2018
DOI: 10.17844/jphpi.v21i1.21263
|View full text |Cite
|
Sign up to set email alerts
|

Aktivitas Antibakteri dari Beberapa Tingkatan Mutu Terasi Udang Rebon

Abstract: Terasi merupakan produk fermentasi ikan atau udang berbentuk pasta padat yang diolah secara tradisional. Bakteri asam laktat dapat diisolasi dari produk terasi dan menghasilkan senyawa antibakteri yaitu bakteriosin. Bakteriosin sebagai pengawet makanan memiliki kelebihan antara lain: dapat mengalami degradasi oleh enzim proteolitik dalam pencernaan manusia sehingga tidak membahayakan untuk kesehatan manusia. Penelitian ini bertujuan menentukan komposisi kimia dan aktivitas antibakteri bakteriosin asam laktat y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 2 publications
0
9
0
5
Order By: Relevance
“…According to [2], lactic acid bacteria having the nature of its ability to give zone clear in medium skim that.The establishment of the zone clear shows that the bacteria is produce a metabolite secondary (lactic acid ) excess so excess lactic acid be made clear zone around the bacteria colonies [3]. Next [4] reported that the ability of forming clear zone vary depending on bacteria type , bakteriosin , 0 (2018) E3S Web of Conferences https://doi.org/10.1051/e3sconf /2018680101 68 10 1 st SRICOENV 2018 17 7 concentration and of the womb nutrients in media .The medium through which recommended to grow lactic acid bacteria is medium MRSA.While the addition of 1 percent CaCO3 aimed at to select lactic acid bacteria which grows on medium and when incubation period is complete 1 x 24 hours will look clear zone around bacteria colonies that grows . It is influenced during incubation period is complete the growth of bacteria lactic acid produces lactic acid that react with CaCO3 that is not soluble in in the medium so as to form calcium lactate that is soluble , with shows that there has been clear regions or zones around bacteria colonies growing [5] Furthermore, the results showed that all isolates had gram-positive characters with purple and rod-shaped cells, while catalase, endospore, and motility were negative.…”
Section: Resultsmentioning
confidence: 99%
“…According to [2], lactic acid bacteria having the nature of its ability to give zone clear in medium skim that.The establishment of the zone clear shows that the bacteria is produce a metabolite secondary (lactic acid ) excess so excess lactic acid be made clear zone around the bacteria colonies [3]. Next [4] reported that the ability of forming clear zone vary depending on bacteria type , bakteriosin , 0 (2018) E3S Web of Conferences https://doi.org/10.1051/e3sconf /2018680101 68 10 1 st SRICOENV 2018 17 7 concentration and of the womb nutrients in media .The medium through which recommended to grow lactic acid bacteria is medium MRSA.While the addition of 1 percent CaCO3 aimed at to select lactic acid bacteria which grows on medium and when incubation period is complete 1 x 24 hours will look clear zone around bacteria colonies that grows . It is influenced during incubation period is complete the growth of bacteria lactic acid produces lactic acid that react with CaCO3 that is not soluble in in the medium so as to form calcium lactate that is soluble , with shows that there has been clear regions or zones around bacteria colonies growing [5] Furthermore, the results showed that all isolates had gram-positive characters with purple and rod-shaped cells, while catalase, endospore, and motility were negative.…”
Section: Resultsmentioning
confidence: 99%
“…Aktivitas proteolitik terjadi karena adanya proses enzimatik dari bakteri asam laktat. Romadhon et al (2018) menyatakan bahwa kandungan protein pada udang rebon berpengaruh terhadap asam glutamat yang dihasilkan selama proses fermentasi. Kandungan protein udang rebon yang tinggi akan menghasilkan asam glutamat yang tinggi pula.…”
Section: Asam Glutamatunclassified
“…Terasi is a popular fermented Indonesian product derived from seafood and served as a condiment-like agent, rich in glutamate which imparts a specific flavor (Prihanto & Muyasyaroh, 2021). The terasi paste contains 25.4-42.5% proteins (Surono & Hosono, 1994a;Ukhty et al, 2017;Romadhon et al, 2018), 23.2-46.4% amino acids (Ali et al, 2020, and 1.51-2.41% total nitrogen (Ukhty et al, 2017;Ali et al, 2020). Nitrogen sources (i.e.…”
Section: Introductionmentioning
confidence: 99%